ANALISIS KEAMANAN WEBSITE LEADS UPNVJ TERHADAP SERANGAN SQL INJECTION & SNIFFING ATTACK - Dimas Perdana Putranto (2022)
LEADS UPNVJ is a system designed for electronic learning purposes for students, which can be accessed online using the Website. On the LEADS UPNVJ website there is important data and it must be kept safe because there is information that is privacy. The types of attacks that are often used to attack a website are SQL injection & Sniffing Attack. SQL injection is an SQL injection attack that can pose a serious security threat to a website, where SQL injection allows attackers to gain access to a website's database which can cause data leaks that make data confidentiality loss, especially for sensitive information. Sniffing Attack is wiretapping and data theft by capturing and monitoring data packet traffic on internet network. Which aims to obtain sensitive data and information. Therefore, through this research, it is hoped that a good analysis can be obtained to measure the security level of the LEADS UPNVJ website. So that if there are weaknesses on the website, it will be analyzed and solutions are obtained to create stronger website security.